Triple Coronary Artery Thrombosis Presenting as Acute Anterior ST-Segment Elevation Myocardial Infarction - Ermis, Emrah; Kahraman, Serkan; Ucar, Hakan; Ozyılmaz, Sinem Ozbay; Allahverdiyev, Samir (International Journal of Angiology, 2018)
Simultaneous multivessel epicardial coronary artery thrombosis is an uncommon finding in acute ST-segment elevation myocardial infarction (STEMI). It generally leads to cardiogenic shock and sudden cardiac death in the hospital. We report a 42-year-old male patient presenting with acute anterior STEMI with triple coronary artery thrombosis. An emergency coronary angiogram showed total occlusion of the left anterior descending artery (LAD) with thrombus formation. At the same time, thrombus formations were also seen in the circumflex artery (CXA), the second obtuse marginal (OM2) branch, and the distal right coronary artery (RCA). We unsuccessfully attempted thrombus aspiration of the LAD. Subsequently, we decided to stent the LAD, and a successful percutaneous coronary intervention (PCI) was performed for the LAD. In a second procedure, RCA thrombosis regressed with 24-hour tirofiban (glycoprotein IIb/IIIa receptor inhibitor) perfusion, although CXA thrombosis and OM thrombosis did not regress. Therefore, we performed stenting of the CXA and OM with a newer provisional technique called the flower petal technique. Thrombolysis in myocardial infarction (TIMI) flow grade III was seen after stenting. The patient was discharged from the hospital 5 days after PCI without any symptoms.
Keywords: multivessel coronary artery disease; artery thrombosis; percutaneous coronary intervention; flower petal technique; acute coronary syndrome; coronary atherosclerosis; coronary stent